Risking capitalism - Soederberg, Susanne, 1966- (Bingley, U.K. : Emerald, 2016)
The growing centrality of risk management in pro-market governance raises important questions regarding how risks are produced, and why? Who and what is included in, and excluded from, risk management, and why? And, what is the relationship between the rise of risk management and neoliberalism? Drawing on various political economy approaches, this volume addresses these questions by examining - both analytically and empirically - diverse meanings and practices of risk management across a range of scales and themes ranging from austerity to climate change to housing and debt. The authors investigate the relationship between shifts in contemporary capitalism and the ways in which neoliberal forms of risk management have emerged, been reproduced and normalized, and, transformed historically.
Introduction - risk management in global capitalism / Susanne Soederberg -- Revanchism, stigma and the production of ignorance: housing struggles in austerity Britain / Tom Slater -- Neoliberalization through housing finance, the displacement of risk, and Canadian housing policy: challenging Minsky's financial instability hypothesis / Alan Walks, Dylan Simone -- A multidimensional approach to urban entrepreneurialism, financialization and gentrification in the high-rise residential market of inner Santiago, Chile / Ernesto Lo<U+0301>pez-Morales -- Financialization of poverty: proletarianizing the financial crisis in post-developmental Korea / Chang Kyung-Sup -- Household debt and the financialization of social reproduction: theorizing the UK housing and hunger crises / Adrienne Roberts -- Navigating the aftermath of crisis and risk in Mexico and Turkey / Thomas Marois, Hepzibah Mun<U+0303>oz-Marti<U+0301>nez -- Accumulating insecurity and manufacturing risk along the energy frontier / Michael Watts -- Risky ventures: financial inclusion, risk management and the uncertain rise of index-based insurance / Marcus Taylor -- The world bank's neoliberal language of resilience / Romain Felli.
Includes bibliographical references.
Print version record
Keywords: Political Science -- Public Policy -- Economic Policy; Political economy; Risk assessment; Financial risk management; Capitalism